Effect of aqueous extract of Glycerrhiza glabra in biochemical and immunological parameters in white Male rats treated with Cyclophosphamide - Ibrahim, Ihsan Resan; AL-phetlawi, Khalil Jadou (Al-Qadisiyah Journal of Pure Science, 2017)
This study was conducted to determine the role of extract of Glycerrhiza glabra to reduce the negative side effects of cyclophosphamide in some biochemical and immunological parameters. To study the effect of extract after treatment, fifteen of White male rats divided into three equal groups first group was injected with distilled water , the second group was injected IP with cyclophosphamide with single dose (50 mg / kg) for 14 days weather the third group was also given the cyclophosphamide with single dose (50 mg / kg) for 14 days then treated animals were given extract at dose (400 mg / kg) for 14 days. Samples of blood were collected for calculate WBCs and phagocytosis , and serum isolated for measurment of the the enzymes GPT, GOT, ALP, glucose, urea and creatinine , the results showed a significant increase p<0.05 in enzymes GPT, GOT, ALP, and creatinine while the results appear decrease in the WBCs ,phagocytic index, glucose and urea level in treated group with drug compared with the control group While the group treated with extract after drug caused significant decrease p<0.05 in enzymes GPT, GOT, ALP, and creatinine .and caused significantly increase in the WBCs ,phagocytic index,glucose and urea level . so that give us conculsion the ability of aqueous extract of Glycerrhiza glabra to reduce the effects of drug cyclophsphamide